Analisis Tingkat Kepedulian Masyarakat Desa Jeladri Winongan Kabupaten Pasuruan Terhadap Kesehatan Lingkungan - Alfani, Mukhammad; Ichwan, Avril Avida; Rahmayani, Devina; Ulumuddin, Ihya'; Purwanto, Shinta Ratu Putri Unon; Lusiana, Nova (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Padang, 2024)
This study aims to analyze the community awareness behavior in Jeladri Village related to environmental health by KKN 72 UINSA Surabaya students, with a special focus on the management of waste and liquid waste generated by households. Through a series of interviews and observations conducted in six hamlets, it was revealed that waste and liquid waste management practices in the village are still done carelessly. For example, many residents burn waste on vacant land or dispose of liquid waste directly on the ground around their homes without adequate treatment. The method used in this research is descriptive qualitative, where purposive sampling technique is applied to obtain relevant information from the selected informants. The results of this study show that the two main factors contributing to this problem are the lack of facilities for waste management and the lack of awareness and knowledge of the community regarding the importance of keeping the environment clean. Therefore, this study emphasizes the urgency of educating the community on proper waste management, as well as the need to improve adequate facilities to support the practice. With these measures, it is hoped that a cleaner and healthier environment can be created, thereby improving the quality of life of the people in Jeladri Village.